Properties of Concrete Under the Influence of Waste Materials as partial Supplement of Aggregate : A Review - Jain, Beauty; Verma, Sandeep (International Journal of Scientific Research in Civil Engineering, 2020)
Concrete is a composite material obtained by using cement, aggregates and water. Few decades ago, these materials were easily available while nowadays there is an adverse effect of the utilization of these materials. During the manufacturing Ordinary Portland Cement (OPC), a large amount of green house gas (CO2) is produced from both industrial and fuel combustion. In industrial process green house gas is emitted due to the heating of limestone (CaCO3) to obtain calcium oxide. Concrete is coined as a primary element of construction industry due to its mechanical and durability properties. Concrete Industry is held responsible for using maximum natural resources in preparation of each element. The utilization of concrete ingredients such as cement and aggregates has been enhanced, which ultimately results in the ill effects on the environment. Basically concrete is a composite material obtained by using cement, aggregates and water. Few decades ago, these materials were easily available while nowadays there is an adverse effect of the utilization of these materials. During the manufacturing Ordinary Portland Cement (OPC), a large amount of green house gas (CO2) is produced from both industrial and fuel combustion. In industrial process green house gas is emitted due to the heating of limestone (CaCO3) to obtain calcium oxide. In this study we are presenting literature survey of journals related to utilization of waste materials.